Psychotherapy of Schizophrenia Works - Karon, Bertram P. (Pragmatic Case Studies in Psychotherapy, 2008)
Davidson (2008), VandenBos (2008), and Silver (2008), well-known experts in the treatment of schizophrenia, have provided very interesting, thought-provoking, and important perspectives on my Case of Mr. X (Karon, 2008) and other such patients. In my response to Davidson, I describe my own problematic clinical experience concerning his positive view of “assertive community treatment.” I also reply to the questions Davidson raises about my clinical techniques and interpretations, e.g., my telling Mr. X that I would not let anyone kill him, my telling Mr. X that he would not become psychotic again under the normal stresses of life, and my intepretation that Mr. X’s not eating was the result of the fear of being poisoned. Finally, I provide an alternative interpretation from Davidson of Freud’s case of the Wolf Man. Because VandenBos and Silver are longtime, supportive colleagues and collaborators, I spend most of my time in responding to their commentaries by emphasizing our points of agreement. Throughout this response, I emphasize my belief that that the powerful ideas in psychoanalysis are not just abstractions, but rather the source of strategies that are very pragmatically helpful in conducting psychotherapy with individuals suffering from schizophrenia.